PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY DAN INTELLECTUAL CAPITAL PADA KINERJA PASAR - Meilany Subadi, Maria Magdalena Ni Made; Wirajaya, I Gde Ary (E-Jurnal Akuntansi; Vol 14 No 3 (2016), 2016)
The company's performance is an important thing to be achieved by each company, because the performance is a reflection of the company's ability to manage and allocate its resources. This study aims to determine the effect of corporate social responsibility disclosure and intellectual capital on the market performance of companies listed in the Indonesia Stock Exchange. The population in this study amounted to 130 manufacturing companies listed in Indonesia Stock Exchange. Method of determining the sample in this study was done by using purposive sampling. The sample in this study amounted to 36 companies Manufacturing. The data analysis technique used in this research is Multiple Linear Regression. The results showed that the corporate social responsibility variable statistically negative effect on market performance Manufacturing company. While the intellectual capital variable was not statistically affect the market performance Manufacturing companies listed in Indonesia Stock Exchange 2011-2014 period.
Keywords: Corporate Social Responsibility, Intellectual Capital, Market Performance